Effect of varied probe length on the resonant frequency of a circular cross-sectional cavity / Mohd Khairul Mohd Salleh ... [et al.] - Mohd Salleh, Mohd Khairul; Suhaili, Mohamad Syukri; Ismail, Zuhani; Awang, Zaiki (Institute of Research, Development and Commercialisation (IRDC), 2005)
A simple design of a metallic circular cross-sectional air-filled cavity is presented. Two probes of varied lengths are used to excite TE112-mode wave into the cavity to give a resonant frequency of 5.86 GHz. The experiments show that the resonant frequency of the cavity resonator decreases as the lengths of the probes are increased. The shortest probe in the range of study gives the closest resonant frequency to the one desired.